2013
DOI: 10.1016/j.msea.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric mechanical properties and tensile behaviour prediction of aluminium alloy 5083 friction stir welding joints

Abstract: The asymmetric material flow, severe plastic deformation and thermal cycle imposed on the base material during friction stir welding (FSW) result in unique microstructural development, which causes a gradient in local mechanical properties in the weld region. Micro-tensile and indentation testing were applied to determine the local mechanical properties in a friction stir welded joint. The local stress-strain curves exhibited a drastic change at the advancing side (AS) due to a steep gradient of mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 28 publications
5
51
0
4
Order By: Relevance
“…6 reveals that the welded joint has a lower hardness as compared with the base material hardness. Rao et al (2013) observed the same trend for the aluminium alloy 5083. The lower value of the hardness is exhibited by softening region, which is shown by all the welded joints at different traverse speed and tool rotational speed.…”
Section: Micro-hardnesssupporting
confidence: 66%
“…6 reveals that the welded joint has a lower hardness as compared with the base material hardness. Rao et al (2013) observed the same trend for the aluminium alloy 5083. The lower value of the hardness is exhibited by softening region, which is shown by all the welded joints at different traverse speed and tool rotational speed.…”
Section: Micro-hardnesssupporting
confidence: 66%
“…The hardness was minimally reduced at TMAZ-NZ on the retreating side, whereas low hardness on the retreating side could lead to the fracture occurred in Figure 8during tensile test. [36] and dissimilar FSW joints [37]. In comparison, dissimilar joints of AA5083-AA6061 showed that hardness value gradually decreased from the advancing side (AA5083), starting from underneath the pin shoulder to the centre of the stir zone.…”
Section: Methodsmentioning
confidence: 96%
“…A medida que se tem ao avanço da ferramenta, forças trativas são exercidas na frente de processo enquanto que, na parte anterior a ferramenta, forças compressivas são dominantes. Além disso, a rotação do pino e a direção de solda são as mesmas para a região de início de deformação da junta (AS -Advancing Side) e opostas na região de redistribuição do metal (RS -Retreating Side), originando uma junta assimétrica, cujas propriedades vão depender da geometria da ferramenta, velocidade de soldagem, penetração, dentre outras variáveis [3]. Na Figura 1 tem-se uma visão geral do processo FSW, assim como alguns aspectos da formação da junta citados acima.…”
Section: Introductionunclassified
“…Na Figura 1 tem-se uma visão geral do processo FSW, assim como alguns aspectos da formação da junta citados acima. A assimetria entre os lados da junta formada pode então afetar a microestrutura da região, a Zona Termicamente Afetada (ZTA) e também a Zona Termomecanicamente Afetada (ZTMA), os quais estão diretamente relacionadas com a integridade da união soldada [3][4]. Desta maneira, neste trabalho foi verificado a influência de parâmetros operacionais como penetração da ferramenta, ângulo de ataque, tipo de ferramenta e modo de controle de penetração (posição ou força), na realização de juntas soldadas topo a topo de chapas de alumínio da liga 3105 H26.…”
Section: Introductionunclassified